2021
DOI: 10.3390/ijerph18094925
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Unhealthy Lifestyle Behaviors on Testicular Function among Healthy Adult Men: A Cross-Sectional Study in Taiwan

Abstract: Recently, the role of lifestyle factors in testicular function has developed into a growing area of interest. Based on cross-sectional data on 3283 Taiwanese men, we investigated whether interactive effects of unhealthy lifestyle behaviors were associated with testicular function. The men were recruited from a private screening institute between 2009 and 2015. Lifestyle behaviors (smoking, alcohol drinking, physical activity (PA), sleeping habits, and diet) were obtained by a validated self-reported questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Moreover, a Chinese cross‐sectional study found a linear association with semen characteristics, 16 whereas another did not find any association between sleep duration and semen characteristics 14 . Similar, a Taiwanese study also reported no association with semen characteristics and reproductive hormone levels 18 …”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, a Chinese cross‐sectional study found a linear association with semen characteristics, 16 whereas another did not find any association between sleep duration and semen characteristics 14 . Similar, a Taiwanese study also reported no association with semen characteristics and reproductive hormone levels 18 …”
Section: Introductionmentioning
confidence: 89%
“…14 Similar, a Taiwanese study also reported no association with semen characteristics and reproductive hormone levels. 18 Other biomarkers of male fecundity, such as testes volume or reproductive hormone levels, have been rarely studied in relation to sleep duration. 4,5 One cross-sectional study from the United States found no association between self-reported sleep duration and testes volume, however, when measuring sleep duration using actigraphy, the authors found a linear association between sleep duration and testes size.…”
Section: Introductionmentioning
confidence: 99%